Analysis of The Relationship Between Managerial Performance, Teaching-Learning Policy and Performance of Inclusive Education System - Basyirah Basyirah; Akhmad Ramli; Darmawanta Sembiring; Alimuddin A. Djawad; Siti Marliah (Journal on Education, 2024)
This study aims to determine inclusive education policies and systems for stakeholders in order to create justice and equal distribution of educational benefits for each student. This study uses a qualitative approach. Data collection was carried out using narrative interview techniques. The results of the study concluded that there were efforts to improve the quality of education, however, the education system still faces significant problems and challenges, one of the challenges experienced by school administrators and the government is the controversy related to special education standards which are considered discriminatory against students with disabilities. The government and school management are also required to provide adequate medical rehabilitation facilities, where these facilities are expected to focus on improving the quality of individual students and overcoming social and environmental barriers. Another result of the study is that researchers identified that regular schools are currently still struggling to implement the principle of inclusivity in its entirety. Policy and cultural transformation is expected to change mindsets and guarantee the rights of students with disabilities and achieve effective and inclusive learning designs.